Not in our genes - "Rose, Steven" (England, 1984)
Not in Our Genes: Biology, Ideology and Human Nature is a 1984 book by the evolutionary geneticist Richard Lewontin, the neurobiologist Steven Rose, and the psychologist Leon Kamin, in which the authors criticize sociobiology and genetic determinism and advocate a socialist society.
Keywords: Biological psychiatry